Lead-carboxylate/polyiodide hybrids constructed from halogen bonding and asymmetric viologen: structures, visible-light-driven photocatalytic properties and enhanced photocurrent responses. Issue 16 (11th April 2018) - Zhao, Li-Ming; Zhang, Wen-Ting; Song, Kai-Yue; Wu, Qi-Qi; Li, Yi; Li, Hao-Hong; Chen, Zhi-Rong
Abstract : Two lead-carboxylate/polyiodide hybrids constructed from halogen bonding and asymmetric viologen have been synthesized, which exhibit efficient photocatalytic degeneration performances. Abstract : The mono-substituted bipyridinium derivative 1-(3-carboxybenzyl)-4, 4′-bipyridinium (cbpy) and polyiodide were adopted to construct two new lead-carboxylate hybrids: [Pb(cbpy)I3 ·I3 ] n (1 ) and {[Pb(cbpy)2 ](I3 )4 ·I2 } n (2 ), in which interesting halogen bonds were detected. Specifically, the hybrids demonstrate efficient photocatalytic degradation of organic dyes and excellent photocurrent response, and the mechanisms of degradation have been discussed and verified using theoretical calculations.